Synthesis and Photophysical Properties of Pyrene-Based Light-Emitting Monomers: Highly Blue Fluorescent Multiply-Conjugated-Shaped Architectures - Hu, Jian-Yong; Yamato, Takehiko (IntechOpen, 2011)
None